Hardware equipment of computer classrooms in Croatian elementary schools - Pavlina, Krešimir (Array, 2012)
With development of information and communication technology computer literacy has become one of basic type of literacy necessary for modern living. Croatian educational strategy acknowledged this necessity and plans to introduce obligatory computer science education from first grade of elementary school. Hardware equipment of computer classrooms presents basic prerequisite for good computer science education. This paper presents research about hardware equipment of computer classrooms in Croatian elementary schools.